Onto-Cartography as a Flat Ontological Method for Meta-Ethical Evaluation of Situated Spatial Planning Values. - Gunder, Michael; Winkler, Tanja (Taylor & Francis, 2021)
This article explores three questions pertaining to ethics and flat ontology. First, what type of ethics might be appropriate to facilitating an inclusive ethics that acknowledges all interacting objects, not just the human, in the world. Second, by what method might a planning ethicist begin to achieve this understanding from a flat ontological perspective. Third, what, if anything, might a meta-ethical lens contribute to a flat ontological perspective. In addressing these questions, a type of assemblage theory called Onto-Cartography, developed by Bryant (2014), will be called on. Planning ethics are predominantly normative ethics concerned with producing a better world by articulating what ought to be done to achieve a desired future. Key here is who defines what is better and who benefits. Within vertical ontologies, these are inevitably human actants. In contrast, meta-ethics is a type of ethics that seeks to comprehend the nature of ethical evaluations so as to determine how a particular ethical value position has emerged in a particular context before attempting to establish what ought to be done. Our application of onto-cartography will focus on explaining, from the perspectives of flat ontology, how specific assemblages in their particular contexts generate their ethical value positions. We also briefly consider if, and how, meta-ethical concerns contribute to such perspectives. We conclude with a discussion as to how to deal with the necessary role of human actants to give meaning and value to ethics and what this implies for flat ontology.
Keywords: Planungstheorie; Ethik; Inklusion; Planungsphilosophie; Norm; Wertung; Bedeutung; Evaluation; Kartographie; Flache Ontologie